CLINICAL PHARMACOLOGY OF DIURETICS - Soldatenko, I. V. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2015)
Clinical pharmacology of diuretics in the international system of ATC (anatomic-therapeutic-chemical) is presented. Classification of this group by the action mechanism and caused effects is provided. Pharmacokinetics and pharmacodynamics features, indications and principles of diuretics usage in clinics are considered. Contraindications, side effects and interaction with other drugs of this group are discussed in detail.